Multi-Locus Sequence Typing and Drug Resistance Analysis of Swine Origin Escherichia coli in Shandong of China and Its Potential Risk on Public Health - Wei Wang; Lanping Yu; Wenwen Hao; Fusen Zhang; Meijie Jiang; Shuping Zhao; Fangkun Wang (Frontiers Media S.A., 2021)
The extensive use of antibiotics has caused antimicrobial resistance and multidrug resistance in Escherichia coli and gradual expands it into a worldwide problem. The resistant E. coli could be transmitted to humans through animal products, thereby creating a problem for bacterial treatment in humans and resulting in a public health issue. This study aims to investigate the molecular typing and drug resistance of swine and human origin E. coli within the same prefecture-level cities of Shandong Province and the potential risk of E. coli on public health. The drug sensitivity results indicated that tetracycline (TE) (97.17%) is a major antibiotic with high drug resistance in 106 swine origin E. coli. There was a significant difference in the drug-resistant genotypes between the two sources, of which the blaTEM positive rate was the highest in the genera of β-lactams (99% in swines and 100% in humans). Among the 146 E. coli isolates, 98 (91.51% swine origin) and 31 (77.5% human origin) isolates were simultaneously resistant to three or more classes of antibiotics, respectively. The multi-locus sequence typing (MLST) results indicate that the 106 swine origin E. coli isolates are divided into 25 STs with ST1258, ST361, and ST10 being the dominant sequence analysis typing strains. There were 19 MLST genotypes in 40 strains of human E. coli from Tai'an, Shandong Province, with ST1193, ST73, ST648, ST131, ST10, and ST1668 being the dominant strains. Moreover, the cluster analysis showed that CCl0 and CC23 were the common clonal complexes (CCs) from the two sources. Our results provide a theoretical basis for guiding the rational use of antibiotics and preventing the spread of drug-resistant bacteria, and also provide epidemiological data for the risk analysis of foodborne bacteria and antimicrobial resistance in swine farms in Shandong Province.